A Descriptive Survey of Elementary PE Teachers’ Readiness for Gamification - Alya Chaeru Nissa; Tedi Supriyadi; Anggi Setia Lengkana (Universitas Negeri Semarang, 2026)
The purpose of the present study is to examine the preparedness of elementary physical education teachers to execute gamification, with regard to cognitive, affective, and behavioral aspects. The current study is based on a quantitative method with descriptive survey research. The sample of the study was 30 physical education teachers of elementary schools located in the region of Sumedang, West Java. Cluster and purposive sampling techniques were used to choose the sample. A validated 5-point Likert scale was used to collect the required data. The results of the study showed that the preparedness of physical education teachers is at the